1998
DOI: 10.1086/515638
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Varicella-Zoster Virus Glycoproteins E and I: Immunologic Responses and Clearance of Virus in a Guinea Pig Model of Chronic Uveitis

Abstract: Guinea pigs immunized with recombinant varicella-zoster virus (VZV) glycoproteins E (gE) and I (gI) developed antigen-specific antibodies in the sera, vitreous, and conjunctival washes. Sera from immunized animals neutralized both cell-free and cell-associated VZV, and peripheral blood lymphocytes proliferated in vitro in response to recombinant gE and gI and to antigens from VZV-infected cells. Immunized guinea pigs were inoculated intravitreally with VZV, which induces chronic uveitis. VZV DNA was more rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…4,5 We have established a system to quantify CMV, EBV, and varicella-zoster virus (VZV) genomes using a 'real-time' quantitative PCR method. [6][7][8] This method measures the accumulation of PCR products with a fluorogenic probe and real-time laser scanning in a 96-well plate, and has a very wide dynamic range. 9 Since this assay does not require additional handling, such as electrophoresis, faster assays with a higher throughput are possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 We have established a system to quantify CMV, EBV, and varicella-zoster virus (VZV) genomes using a 'real-time' quantitative PCR method. [6][7][8] This method measures the accumulation of PCR products with a fluorogenic probe and real-time laser scanning in a 96-well plate, and has a very wide dynamic range. 9 Since this assay does not require additional handling, such as electrophoresis, faster assays with a higher throughput are possible.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The PCR primers and probe for HHV6 were selected from the U31 gene (large tegment protein). The upstream primer was 5′-TTTGCAGTCATCACGAT-CGG-3′, and downstream primer was 5′-AGAGCGACAAATTGGAGGTTTC-3′.…”
Section: Real-time Quantitative Pcr Assaymentioning
confidence: 99%
“…Studies with gE subunit vaccines already demonstrated the induction of specific B and T-cell responses in animals. 42,43 Interestingly, preliminary results from an open randomized study in adults exploring a recombinant gE vaccine with adjuvant for zoster prevention demonstrated more robust cellular (i.e. CD4) and humoral immune responses in older adults compared to the application of a live varicella vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we established a quantitative real-time polymerase chain reaction (PCR) assay to quantify the VZV genome copies (8). Using this assay, we observed that there was a higher occurrence of viremic VZV in varicella than in zoster, and that acyclovir treatment marked-*Address correspondence to Dr. Yoshinori Ito, Department of PediatricslDevelopmental Pediatrics, Nagoya University Graduate School of Medicine, 65 Tsurumai-cho, Showa-ku, Nagoya, Aichi 466-8550, Japan.…”
mentioning
confidence: 99%
“…Whole blood was obtained from the patients, and plasma and PBMC were separated by density gradient with Ficoll-Paque (Pharmacia Biotech, Uppsala, Sweden). The real-time quantitative PCR assay was performed using a TaqMan PCR kit and a Model 7700 Sequence Detector (PE Applied Biosystems, Foster City, U.S.A.), as previously described (8,9). Primers to amplify the glycoprotein B (gB) and ORF62 genes were selected.…”
mentioning
confidence: 99%